Balance Changes in Adult Cancer Survivors Participating in a 16-Week Therapeutic Yoga Program - Mark J. Miller BS; Daniel C. Hughes PhD; Nydia T. Darby DPT; Tim Calderon MS; Darpan I. Patel PhD; Monica C. Serra PhD; Amelie G. Ramirez Dr. PH; Alexis Ortiz PT, PhD; Gustavo J. Almeida PT, PhD (Integrative Cancer Therapies)
Introduction: Balance problems arising from cancer and its treatments can significantly impact daily functionality and quality of life. Improving balance as part of a cancer treatment plan could result in better patient outcomes. Thus, the aim of this study was to determine whether an integrative therapeutic yoga intervention can improve balance in a heterogenous population of cancer survivors (CS). Methods: This is a secondary analysis of data from a 16-week feasibility study where therapeutic yoga was supplemented with psychosocial support to maximize health-related quality of life in adult CS of any stage and site. In this study, we investigated balance, as it has been shown to be an important outcome in CS due to its role in physical function and quality of life. The intervention included therapeutic yoga three times per week for 16 weeks and daily psychosocial support provided via text message. Participants’ balance was assessed while standing on a pressure mat with feet together, eyes opened and closed, for 30 seconds in each condition. Data on the “sway path distance” (displacement of the center of gravity) in the two conditions were obtained. Changes in balance after the intervention (from baseline to follow-up) were analyzed using paired-sample t-tests. Changes in balance were also assessed using responder analysis. We described the proportion of participants that improved their balance or not based on 10% difference from baseline scores. Results: Of the 29 participants included, 22 (76%) completed post-assessments. Changes in both balance assessment conditions were not statistically significant (eyes opened: 80.06 ± 374.99, p  = .702; eyes closed: −1.82 ± 24.01, p  = .068). Responder analysis showed that 8 participants improved their balance with eyes opened, while 8 worsened, and 6 did not change. Analysis of balance with eyes closed showed that 5 improved, 8 worsened, and 9 did not change. Conclusion: This secondary analysis of data from a heterogenous cohort of adult CS did not support our hypothesis at the group level. However, at the individual level, responder analysis indicated improved balance in some survivors. Future research is needed to determine factors related to the cancer experience which might mediate balance outcomes to inform better integrative interventions.